POLITIK HUKUM EKONOMI SYARIAH DALAM PERKEMBANGAN LEMBAGA KEUANGAN SYARIAH DI INDONESIA - Mul Irawan (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2018)
Sharia economy has grown rapidly in Indonesia. This indicated by the creasing number of bank and non-bank finansial institution used sharia principles. One way’s to support these development is the sharia law political economy which conducted by the government. The problem who must be examined integrally was the politic role of law in the sharia finansial institutions development and the sharia finansial institutions development itself. The purpose and benefits of this research were to provide an objective picture as well as a recommendation for the strengthening the Islamic politic of law and sharia regulations. This research used normative method, which was a study on regulation, research result, journal, data and other reference, that would be analyzed by qualitative descriptive method. The results of the study found that the politic of laws and regulations of sharia economy have being contributed and established facilities for the development of Islamic finansial institutions in Indonesia. The unity of politic on law and sharia economic regulation has established public trust and provided an opportunities and protection for community, bussiness people, customers and sharia finansial institutions